Mohd Najib : selepas tsunami Cina - A. Kadir Jasin, 1947- (Kuala lumpur : Berita Publishing Sdn. Bhd., 2013)
On political issues after the general election of 2013 governance by Mohd Najib in Malaysia.
Includes index.
In Malay.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Prime minister -- Malaysia; Mohd najib Tun Haji Abdul Razak, Dato' Sri, 1953-; Politician -- Malaysia; Elections -- Malaysia; Politics and government -- Malaysia